2017
DOI: 10.1111/nyas.13551
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers of low back pain and disc degeneration: a review

Abstract: Biomarkers are biological characteristics that can be used to indicate health or disease. This paper reviews studies on biomarkers of low back pain (LBP) in human subjects. LBP is the leading cause of disability, caused by various spine-related disorders, including intervertebral disc degeneration, disc herniation, spinal stenosis, and facet arthritis. The focus of these studies is inflammatory mediators, because inflammation contributes to the pathogenesis of disc degeneration and associated pain mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
221
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(243 citation statements)
references
References 86 publications
1
221
1
9
Order By: Relevance
“…). Multiple studies have identified immune cells after IVD injury and degeneration, including macrophages, T lymphocytes, and mast cells (Table ), as well as important proinflammatory cytokine responses . While some studies demonstrate a weak immune response in herniated tissue and with induced AF injury in animal models, repeated injury is known to increase that proinflammatory condition .…”
Section: Cellular Responses To Injurymentioning
confidence: 99%
“…). Multiple studies have identified immune cells after IVD injury and degeneration, including macrophages, T lymphocytes, and mast cells (Table ), as well as important proinflammatory cytokine responses . While some studies demonstrate a weak immune response in herniated tissue and with induced AF injury in animal models, repeated injury is known to increase that proinflammatory condition .…”
Section: Cellular Responses To Injurymentioning
confidence: 99%
“…This is an emerging field and new biomarkers are being developed that can distinguish different sources of back pain. Serum biomarkers are quantitative and objective measurements, and can be used as indicators of biological processes involved in discogenic pain or as indicators for systematic disorders such as osteoporosis . Currently reported candidates for serum biomarkers for back pain include C‐C motif ligand 5, C‐X‐C motif ligand 6, IL‐6, high‐sensitivity C‐reactive protein, TNF‐α, IL‐1β, and type 2 collagen .…”
Section: Noninvasive Diagnostic Tools For Discogenic Painmentioning
confidence: 99%
“…Serum biomarkers are quantitative and objective measurements, and can be used as indicators of biological processes involved in discogenic pain or as indicators for systematic disorders such as osteoporosis. (52) Currently reported candidates for serum biomarkers for back pain include C-C motif ligand 5, C-X-C motif ligand 6, IL-6, high-sensitivity C-reactive protein, TNF-a, IL-1b, and type 2 collagen. (52)(53)(54)(55)(56)(57)(58)(59) Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has also been shown to distinguish discogenic LBP from the other forms of chronic back pain, and complement C3 and fibrinogen are potential serum biomarkers for discogenic back pain.…”
Section: Noninvasive Diagnostic Tools For Discogenic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…IDD is a multifactorial, cell‐mediated process originating in the NP in which normal tissue turnover becomes imbalanced, favoring degradation over formation . This degradative environment is known to include metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)—catabolic enzymes that respectively degrade the two main constituents of the IVD, collagen and aggrecan .…”
Section: Introductionmentioning
confidence: 99%